The social cost of carbon - Richard S. J. Tol (The Economic and Social Research Institute (ESRI), 2011)
This paper surveys the literature on the economic impact of climate change. Different methods have been used to estimate the impact of climate change on human welfare. Studies agree that there are positive and negative impacts. In the short term, positive impacts may dominate, but these are largely sunk. In the longer term, there are net negative impacts. Poorer people tend to be more vulnerable to climate change. There is a trade-off between development policy and climate policy. Estimated aggregate impacts are not very large, but they are uncertain and incomplete. Estimates of the marginal impacts suggest that greenhouse gas emissions should be taxed, and that the emission reduction targets announced by politicians are probably too ambitious.
Keywords: 330; climate policy; carbon dioxide emission reduction; cost-benefit analysis